Seasonality in anthropogenic aerosol effects on East Asian climate simulated with CAM5. Issue 20 (20th October 2015) - Jiang, Yiquan; Yang, Xiu‐Qun; Liu, Xiaohong
Abstract: This study investigates the seasonality in anthropogenic aerosol optical depth (AOD) distributions and their effects on clouds and precipitation in East Asia with the Community Atmospheric Model version 5. The differences between the model experiments with and without anthropogenic emissions exhibit a northward shift of the maximal AOD change in East Asia from March to July and then a southward withdrawal from September to November, which are induced by East Asian monsoon circulation. Associated with the shift, the direct and semidirect effects of the anthropogenic aerosols are the most pronounced in spring and summer, with a maximum center in North China during summer and a secondary center in South China during spring. The cloud liquid water path and shortwave cloud forcing changes, however, are the weakest in North China during summer. The indirect effect is the strongest in South China during spring, which is related to the large amount of middle‐low level clouds in cold seasons in East China. A positive feedback between aerosol induced surface cooling and low‐level cloud increase is identified in East China, which acts to enforce the aerosol indirect effect in spring. Accordingly, the climate response to the anthropogenic aerosols is also characterized by a northward shift of reduced precipitation from spring to summer, leading to a spring drought in South China and a summer drought in North China. The spring drought is attributed to both direct and indirect effects of the anthropogenic aerosols, while the summer drought is primarily determined by the aerosols' direct effect. Key Points: Anthropogenic aerosols have the strongest direct (indirect) effect in China during summer (spring) Monsoon circulation induces a northward shift of the maximal AOD over China from spring to summer The aerosol effects lead to a spring drought in South China and a summer drought in North China